Affect Expression and Self-Regulation Capacities of Infants Exposed in utero to Psychotropics - Reebye, Pratibha N.; Ng, Tammy W.; Misri, Shaila; Stikarovska, Irena (Frontiers in Psychiatry, 2012)
This study explored the affect expression and self-regulation capacities of eight month old infants exposed in utero to psychotropic medications. This is a continuation of our previous study conducted on the same cohort when infants were three months old. Psychotropics implicated are antidepressant medications: selective serotonin reuptake inhibitors (SSRI), and a benzodiazepine derivative anxiolytic (clonazepam). The three comparison groups were: control (n=23) (infants gestationally non-exposed to psychotropics), SSRI-alone (n=22) (infants exposed to SSRIs only and having mothers who had a primary diagnosis of depressive disorder without having comorbid anxiety disorder), and SSRI+ group (n=15) (infants gestationally exposed to SSRIs and Clonazepam and having mothers that had both clinical depression and anxiety disorder). Thirty-seven participants from the initial cohort were recruited. Using the Parent Child Early Relational Assessment Scale (PCERA), infants were assessed in a dyadic context during free play and a structured task. There were clear significant differences in psychotropic exposed and non-exposed dyads regarding infant negative affect management. Notable findings were that the SSRI+ group mothers showed significant associations with only one infant affect: i.e. infant negative affect. This group of mothers also showed significant associations with infant’s averting and avoiding behaviors. These associations were seen in both free play and structured task situations signifying probable established pattern. SSRI-alone group was similar to control mothers and showed variable associations with infant’s positive, negative and sober moods unlike SSRI+ group. There were no differences in infants’ capacity for self–regulation in psychotropic exposed and non-exposed groups. Increased awareness of these vulnerable subgroups (SSRI-alone and SSRI+) is needed, in order to safeguard these dyads through better support systems and improved management.